Noninvasive diagnostic method for idiopathic portal hypertension based on measurements of liver and spleen stiffness by ARFI elastography - Furuichi, Yoshihiro; Moriyasu, Fuminori; Taira, Junichi; Sugimoto, Katsutoshi; Sano, Takatomo; Ichimura, Shigeki; Miyata, Yuki; Imai, Yasuharu (Journal of gastroenterology, 2013)
Background Acoustic radiation force impulse (ARFI) elastography is an ultrasound technique that is capable of measuring tissue stiffness noninvasively. It is difficult to differentiate idiopathic portal hypertension (IPH) from liver cirrhosis (LC) or chronic hepatitis (CH), and liver biopsy is essential. We investigated whether it would be possible to noninvasively diagnose IPH by measuring the stiffness of the liver and spleen by ARFI. Methods The subjects were 17 IPH patients, 25 LC patients, 20 CH patients, and 20 normal controls (NC). We measured liver stiffness, spleen stiffness, and the spleen/liver stiffness ratio, and plotted ROC curves. Results The median value of liver stiffness in the IPH group was lower than that in the LC group ( p = 0.00077) and about the same as in the CH group ( p = 0.79). The median value of spleen stiffness was highest in the IPH group (IPH vs. LC group, p = 0.003; IPH vs. CH group, p < 0.00001). The spleen/liver stiffness ratio was lower in the LC group and in the CH group, and higher in the IPH group ( p < 0.001, respectively). When an ROC curve of spleen/liver stiffness ratios was plotted to differentiate between the IPH group and the combined group of patients with other liver diseases (LC + CH group), when a cutoff value of 1.71 was used, the AUROC was 0.933 sensitivity 0.941, specificity 0.800, and accuracy 0.839. Conclusion Measuring the spleen/liver stiffness ratio by ARFI made it possible to noninvasively, specifically, and accurately diagnose IPH.